The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5935/0103-507x.20220145-en
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the management and prevention of withdrawal syndrome in critically ill pediatric patients: a systematic review

Abstract: Objective To verify strategies for the prevention and treatment of abstinence syndrome in a pediatric intensive care unit. Methods This is a systematic review in the PubMed database ® , Lilacs, Embase, Web of Science, Cochrane, Cinahl, Cochrane Database Systematic Review and CENTRAL. A three-step search strategy was used for this review, and the protocol was approved in PROSPERO (CRD42021274670). Results Twelve arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Notably, CPGs focused on delirium were lacking, which is consistent with current clinical practice surveys (9)(10)(11). Additionally, a recent review of IWS implementation strategies found similarities to the IWS summary recommendations (61).…”
Section: Discussionsupporting
confidence: 61%
“…Notably, CPGs focused on delirium were lacking, which is consistent with current clinical practice surveys (9)(10)(11). Additionally, a recent review of IWS implementation strategies found similarities to the IWS summary recommendations (61).…”
Section: Discussionsupporting
confidence: 61%